Analysis of the Influence of Service Quality, Facilities and Value Rates on Patient Interest through Inpatient Satisfaction at Islam Malahayati Hospital - Saparuddin Siregar; Yenni Samri Juliati Nst; Rafia Hafni Harahap (Budapest International Research and Critics University, 2021)
This study aims to analyze the effect of service quality, facilities and tariff rates on patient interest through inpatient satisfaction at Islam Malahayati Hospital Medan. This research method uses a quantitative approach with path analysis and uses the assistance of the SPSS program version 20.0. This study used a questionnaire with a sample of 56 respondents with data collection. The results of the study based on a partial test show that the Service Quality variable has a positive and significant effect on Patient Satisfaction at Islam Malahayati Hospital Medan, and the tariff value variable has a positive and significant effect on patient satisfaction and the Facility variable has a positive and significant effect on Patient Satisfaction. Then service quality has a positive and significant effect on patient interest in Malahayati Hospital, and service facilities have a positive and significant effect on patient interest. The tariff value has a positive and significant effect on patient interest and patient satisfaction has a positive and significant effect on patient interest. While the results of the study based on the simultaneous test showed that the variables of Service Quality, Facilities and Value Rates had a positive and significant effect on patient satisfaction through patient interest. The implications of this study indicate that through good service to patients it will be able to increase patient satisfaction so that it has an impact on patient satisfaction and patient interest. Facilities that have been determined by the hospital can be reached by the patient and can increase patient visits as well as the value of the rate can be measured through benefits or from what has been provided by the hospital if the facilities provided by the hospital are complete and can fulfill the patient's wishes, it will have a good impact on the development and success of the hospital.